2023
DOI: 10.1021/acsomega.3c01662
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites from Lactococcus lactis subsp. lactis: Isolation, Structure Elucidation, and Antimicrobial Activity

Vishwambar D. Navale,
Balasaheb R. Borade,
Gamidi Rama Krishna
et al.

Abstract: Herein, we disclose the identification of novel metabolites from a potential probiotic strain, Lactococcus lactis subsp. lactis, obtained from traditional dairy milk samples collected in Maharashtra, India (in January 2021). Isolated metabolites include pyrazin-2-carboxamide [1, pyrazinamide, a potential antitubercular drug], 3,5-dihydroxy-6-methyl-2,3-dihydro-4H-pyran-4-one (2, DDMP), 2,4-di-tert-butylphenol (3), and hexadecanoic acid (4, palmitic acid). The chemical structures of these metabolites were eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…These findings were based on phenotypic and sequencing analyses. Early research has led to the strong notion that dairy products, such as milk, yogurt 28 , 29 , cheese and sourdough 30 , 31 are the primary source of Lactococcus sp . Nonetheless, accumulating evidence from multiple studies has demonstrated the isolation of Lactococcus species from non-dairy sources such as fresh vegetables 32 , fruits 33 , leaves 34 , and silage 35 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings were based on phenotypic and sequencing analyses. Early research has led to the strong notion that dairy products, such as milk, yogurt 28 , 29 , cheese and sourdough 30 , 31 are the primary source of Lactococcus sp . Nonetheless, accumulating evidence from multiple studies has demonstrated the isolation of Lactococcus species from non-dairy sources such as fresh vegetables 32 , fruits 33 , leaves 34 , and silage 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Gajbhiye et al [16] isolated and purified antifungal compounds such as cyclo-dipeptide from L. lactis, demonstrating the potential of L. lactis to be applied to fungal control in food preservation. Navale et al [17] found that L. lactis collected from milk showed effective inhibition of fungi because of the presence of metabolites such as phenolic compounds. Hence, considering the probiotic function and potential antifungal activity of L. lactis, it was expected to be incorporated as an ideal bioactive substance to enhance the antifungal properties of the GN coating.…”
Section: Introductionmentioning
confidence: 99%